2010
DOI: 10.1103/physrevd.81.084035
|View full text |Cite
|
Sign up to set email alerts
|

Generation of circular polarization of the CMB

Abstract: According to the standard cosmology, near the last scattering surface, the photons scattered via Compton scattering are just linearly polarized and then the primordial circular polarization of the CMB photons is zero. In this work we show that CMB polarization acquires a small degree of circular polarization when a background magnetic field is considered or the quantum electrodynamic sector of standard model is extended by Lorentz-noninvariant operators as well as noncommutativity. The existence of circular po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 38 publications
0
50
1
Order By: Relevance
“…polarization by the Compton scattering is possible [11]. Meanwhile, it is recently shown that the photons of a linearly polarized laser beam can acquire circular or B-mode linear polarization by scattering off active neutrinos via a parity violation process.…”
Section: Jhep02(2017)003mentioning
confidence: 99%
“…polarization by the Compton scattering is possible [11]. Meanwhile, it is recently shown that the photons of a linearly polarized laser beam can acquire circular or B-mode linear polarization by scattering off active neutrinos via a parity violation process.…”
Section: Jhep02(2017)003mentioning
confidence: 99%
“…Sawyer has discussed the CP due to photon-photon interactions mediated by neutral hydrogen background [16]. In addition, some new physics effects can induce the CP of the CMB [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11], the angular power spectrum of CMB circular polarizations and relevant correlations are studied in the case that circular polarization is generated by photon-electron scattering in the presence of magnetic fields. I is shown that Lorentz symmetry violation in some extension of standard model for particle physics [9,12] and an axion-like cosmological pseudoscalar field [13] can generate the CMB circular polarization. Ref.…”
mentioning
confidence: 99%
“…[8,9] present the role of background magnetic fields in producing the CMB circular polarization, and ∆φ F C ∼ 10 −19 for micro gauss magnetic fields. In refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation